Comparative Analysis of RISC and CISC Architectures in Modern Embedded System Development - Roynaldy Rosdiyanto; Siti Fatimatul Zuhro; Refi Nisfuwadi (Komunitas Dosen Indonesia, 2025)
Computer architecture plays a crucial role in the development of embedded systems, particularly in the era of the Internet of Things (IoT), edge computing, and intelligent devices with low battery power. The two main approaches in computer architecture, namely RISC (Reduced Instruction Set Computing) and CISC (Complex Instruction Set Computing), each have their own advantages and disadvantages in terms of efficiency, speed, and energy consumption. This study aims to compare and analyze the performance of both architectures in the development of modern embedded systems, focusing on several parameters such as instruction efficiency, memory usage, interrupt response time, and support from toolchains and developer ecosystems. This research employs both qualitative and quantitative methods based on a literature review of 20 recent international journals (2020–2025), as well as case studies of implementations on ARM Cortex (RISC), RISC-V, and embedded x86 processors (CISC). The analysis results show that RISC architectures, particularly RISC-V, offer better flexibility, modularity, and energy efficiency, making them well-suited for low-power and real-time applications. However, CISC architectures remain superior in terms of backward compatibility, structured instruction complexity, and broad industry support for traditional applications. The study concludes that the selection of an architecture should consider several factors, including energy efficiency, design complexity, and ecosystem support, according to the specific requirements of the embedded system being developed